Neutrosophic Soft Rough Sets for Optimizing Rural Legal Aid: A Novel Approach to Rural Revitalization - Yan Sui (Neutrosophic Sets and Systems)
Rural revitalization initiatives are gaining global momentum as governments strive to bridge the urban-rural divide and promote inclusive development. However, the delivery of legal aid in rural contexts is often hindered by uncertainty, incomplete information, cultural diversity, and resource constraints. To address these challenges, this research paper proposes a novel decision-making framework based on Neutrosophic Soft Rough Sets (NSRS) to address to optimize rural legal aid planning. The proposed NSRS model integrates the strengths of soft sets, rough sets, and neutrosophic logic to manage vagueness and inconsistency in legal aid data. A real-world case study involving 30 rural villages and six critical evaluation criteria is presented to assess the applicability of our framework. Decision rules and prioritization strategies are derived using the NSRS model to guide equitable and efficient legal aid distribution. The reported results reveal that the NSRS-based approach significantly improves decision quality, adaptability, and fairness compared to other neutrosophic models.